Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species - Etzler, Frank E. (Zootaxa, 2020)
Three new North American species of Paradonus Stibick are described: Paradonus gallatinensis new species, Paradonus gustafsoni new species and Paradonus stibicki new species is described for specimens formerly called Paradonus pectoralis sensu Stibick, 1991. The type species of the genus, Paradonus pectoralis Say, 1839 is redefined, and the Holotype of Paradonus olivereae Stibick, 1991 is designated as the Neotype of P. pectoralis, a common, widespread species. The genus is redescribed, a checklist of species is included, and notes on the described species north of Mexico are given. Hypnoidus guatemalensis Champion, 1895 is removed from the genus and placed in Zorochros Thompson, 1858 as Zorochros guatemalensis (Champion, 1895) new combination. A key to all described species north of Mexico is provided, along with illustrations of characters used in identifying species.